Metal versus plastic stents in the management of benign biliary strictures: systematic review and meta-analysis of randomized controlled trials. Issue 5 (14th February 2022) - Kamal, Faisal; Ali Khan, Muhammad; Lee-Smith, Wade; Sharma, Sachit; Acharya, Ashu; Imam, Zaid; Jowhar, Dawit; Esswein, Julia; Kothadia, Jiten; Aziz, Muhammad; Chandan, Saurabh; Arain, Mustafa; et al.
Abstract : Benign biliary strictures (BBS) are usually treated with endoscopic retrograde cholangiopancreatography (ERCP) with the placement of multiple plastic stents (MPS) or a covered self-expandable metal stent (CSEMS). In this meta-analysis, we compared the efficacy and safety of MPS and CSEMS in the management of BBS. We reviewed several databases from inception to 28 April 2021 to identify RCTs that compared MPS with CSEMS in the management of BBS. Our outcomes of interest were stricture resolution, stricture recurrence, adverse events, stent migration and mean number of ERCPs to achieve stricture resolution. Data were analyzed using a random-effects model. We included eight RCTs with 524 patients. We found no significant difference in the rate of stricture resolution (risk ratio, 1.02; 95% CI, 0.96–1.10), stricture recurrence (risk ratio, 1.68; 95% CI, 0.72–3.88) or adverse events (risk ratio, 1.17; 95% CI, 0.73–1.87) between groups. Mean number of ERCPs was significantly lower in the CSEMS group (SMD, −1.99; 95% CI, −3.35 to −0.64). The rate of stent migration was significantly higher in the CSEMS group. CSEMS are comparable in efficacy and safety to MPS in the management of BBS but require fewer ERCPs to achieve stricture resolution.